GOODBYE CURRENCY (IN THE APPROACH TO ECONOMIC LAW AND SHARIA ECONOMIC LAW) - Encep Ahmad Yani; Haswar Widjajanto (SEAN Institute, 2023)
Provisions of Article 15 paragraph (1) of Law Number 30 of 2004 Concerning the Position of a Notary (UUJN) in conjunction with Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of a Notary (UUJN-P) Notaries are subject to the right to making official deeds, including making inheritance certificates for Indonesian citizens in the form of notary deed (partij akten). Likewise with the provisions of Article 111 paragraph (1) letter c Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 16 of 2021 concerning the Third Amendment to the Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 concerning Provisions for Implementing Regulations Government Number 24 of 1997 Concerning Land Registration is the legal basis for the power of a notary to make a deed of inheritance for Indonesian citizens regardless of class, ethnicity and religion of the heirs. Preparation of legal documents. Inheritance SPT before a notary for Indonesian citizens is made in the form of an authentic deed, so the strength of proof is perfect, therefore binding on the heirs and other related parties.